Integrating Addie and Competency-Based Assessment for Student Pilot Performance Evaluation - Hadi Prayitno; Parjan; Dhian Supardam; Fachrurrazi Burhanuddin (Politeknik Penerbangan Indonesia Curug, 2026)
This study develops and evaluates a structured assessment model integrating the ADDIE instructional design framework with competency-based evaluation to improve student pilot performance measurement. The research applies a research and development approach involving design validation, limited trials, and implementation in flight training. The proposed model, SIM-FLIGHT, assesses both technical and non-technical competencies, including flight performance, safety awareness, and decision-making skills. Data were collected using validated assessment instruments and analyzed through pretest–post-test comparison, N-Gain analysis, and statistical testing. The results indicate a significant improvement in overall student performance, particularly in non-technical competencies, demonstrating the effectiveness of a systematic and measurable evaluation framework. The findings suggest that integrating structured instructional design with competency-based assessment enhances objectivity, feedback quality, and training outcomes in aviation education.